Molecular recognition study of β-cyclodextrin and its two derivatives with some aliphatic guests by competitive inclusion method - You, Chang Cheng (2011)
Spectrophotometric titrations were performed in aqueous buffer solution ( pH = 10. 5 , c =0. 025 mol/ L) at 25ᵒC determine the binding constant s of β-cyclodextrin (β-CD) , mono (6-O-α-malto-syl)- β-cyclodextrin (6-G2-β-CD) and mono [2-O-(2-hydroxypropyl)]-β-cyclodextrin (2-HP-β-CD) with several aliphatic chiral guest molecules using phenolphthalein as a spectral probe. The results obtained indicate that several weak interactions cooperatively contribute to the inclusion complexation of the β-cyclodextrin hosts and the complex stability is dominated by the size/shape-matching between host and guest. The substituent on the cyclodextrin derivatives changes it s original binding ability. For the relatively small guest molecules, i. e. , borneol , camphor and menthol , the molecular binding ability is 2-HP-β-CD > β-CD >6-G2-β-CD. Furthermore, the three β-cyclodextrin host s can also serve as chiral discrimination reagents and afford stronger binding ability toward ( + )-isomers. Among them, 2-HP-β-CD gives a moderate enantiometric selectivity of 1. 25 for ( + ) / ( - )-camphor.